Design and development of a pneumatic powered lower limb exoskeleton for assistive mobility application - Tay, Eugene Yao Zhong. (2009)
Exoskeletons are built to be wearable and to improve human locomotion that increase the speed, strength and the endurance of the user. Singapore faces a rapid ageing population and a common disability among the elderly is their mobility. This project is to design and fabricate a lower limb exoskeleton, which can assist the elderly or rehabilitative patients in walking. The exoskeleton is designed to support the user’s lower limb during walking. The movement of the exoskeleton is to follow the human normal walking gait. The exoskeleton has been designed with the considerations of movements in the sagittal plane and assuming that the user still has the ability to balance and walk.